2020
DOI: 10.3390/ijms21031168
|View full text |Cite
|
Sign up to set email alerts
|

Is Sleep Disruption a Cause or Consequence of Alzheimer’s Disease? Reviewing Its Possible Role as a Biomarker

Abstract: In recent years, the idea that sleep is critical for cognitive processing has gained strength. Alzheimer's disease (AD) is the most common form of dementia worldwide and presents a high prevalence of sleep disturbances. However, it is difficult to establish causal relations, since a vicious circle emerges between different aspects of the disease. Nowadays, we know that sleep is crucial to consolidate memory and to remove the excess of beta-amyloid and hyperphosphorilated tau accumulated in AD patients' brains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 144 publications
(177 reference statements)
0
43
0
2
Order By: Relevance
“…For example, recent cross-sectional studies suggest that SWS may be more related to Aβ (Mander et al, 2015), while spindle coupling may be more related to tau pathology (Winer et al, 2019). Therefore, it has been suggested that sleep itself could be used as an early marker of preclinical AD (Hita-Yanez et al, 2013;Jelicic et al, 2002;Ju et al, 2013;Lloret et al, 2020;Winer et al, 2019). Assessing sleep is a relatively non-invasive method in comparison with CSF or PET scans.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, recent cross-sectional studies suggest that SWS may be more related to Aβ (Mander et al, 2015), while spindle coupling may be more related to tau pathology (Winer et al, 2019). Therefore, it has been suggested that sleep itself could be used as an early marker of preclinical AD (Hita-Yanez et al, 2013;Jelicic et al, 2002;Ju et al, 2013;Lloret et al, 2020;Winer et al, 2019). Assessing sleep is a relatively non-invasive method in comparison with CSF or PET scans.…”
Section: Future Directionsmentioning
confidence: 99%
“…Scientific evidence supports the relationship between sleep-wake disturbances and episodic memory (Inostroza & Born, 2013; Lloret et al, 2020). Sleep promotes the consolidation of episodic memory by the replaying of neural activities occurring in the hippocampal and extrahippocampal regions, including the neocortical and striatal networks during sleep.…”
mentioning
confidence: 81%
“…Sleep promotes the consolidation of episodic memory by the replaying of neural activities occurring in the hippocampal and extrahippocampal regions, including the neocortical and striatal networks during sleep. Sleep-wake disturbances may disrupt consolidation because they interrupt neural reactivation in the hippocampal and extrahippocampal regions (Inostroza & Born, 2013; Lloret et al, 2020). One reason the relationship between sleep-wake disturbance and episodic memory loss in older adults is equivocal is because studies have used exclusively objective or perceived measures of sleep-wake disturbances (Yeh et al, 2018), which may impede fully understanding of sleep-wake disturbances.…”
mentioning
confidence: 99%
“…There also appears to be a bi-directional relationship between dementia and sleep, with sleep disruption representing both a risk factor for, and symptom of, the neurocognitive syndrome [233][234][235]. A recent systematic review and metanalysis found that sleep problems, including both short and long sleep duration, insomnia, OSA, impaired circadian rhythm and sleep quality, were associated with an increased relative risk of preclinical AD, cognitive impairment and AD [236].…”
Section: Dementiamentioning
confidence: 99%